(untitled) (Community Based Medical Journal, 2022)
Introduction: Some studies have shown the possible involvement of Helicobacter pylori (H. pylori) infection in chronic idiopathic urticaria, but the relationship remains controversial. The aim of this study was to quantitatively assess the association between H. pylori infection and chronic idiopathic urticaria. Material & Methods: A case-control type of analytical study was conducted in the department of Dermatology and Venereology, Naval Base Hospital (BNS Patenga), Chattogram, Bangladesh for duration of 06 months. Total 50 patients were enrolled in this study. 25 Patients of CIU with no identifiable cause were taken as case and patients without urticaria were taken as control, attending in the outpatient department. H. pylori infection was confirmed by Serum IgG for H. pylori test. Results: The result shows that Helicobacter pylori significantly affect a high percentage of patients with chronic idiopathic urticaria and response to eradication therapy was evident in more patients in whom H. pylori were eradicated. Conclusion: The study shows that Helicobacter pylori significantly affects a high percentage of patients with CIU. Response to eradication therapy was evident in more patients in whom H. pylori was eradicated while few patients showed no response despite eradication of H. pylori. The result of this study suggests that H. pylori infection should be included in diagnostic work up of patients with no response to usual treatment for CIU. CBMJ 2021 January: vol. 10 no. 02 P: 75-79